Prediction of shuttle run test target scores in Japanese female judo participants - Sogabe, A.; Sonoda, R.; Tanabe, M.; Tokuno, K.; Hikage, N.; Shirase, H.; Deguchi, T.; Nanjo, M.; Kaiyama, H.; Shintani, M.; Nakamura, H.; Koyama, K.; et al. (Association for the Scientific Studies on Judo, Kodokan, 2013)
Purpose: To predict the target score of the shuttle run test (S-test) in Japanese female judo participants. Methods: A total of 54 female national judo participants of the Japan Judo Federation in seven weight categories (48 kg, n=9; 52 kg, n = 5; 57 kg, n = 12; 63 kg, n=6; 70 kg, n = 8; 78 kg, n = 7; and >78 kg, n=7) performed the S-test. Participants ran back and forth on a 20-m course in time to a prerecorded audio beep. Each time they touched the 20-m marker, the tempo of the beeps increased, and participants were required to increases their pace accordingly. When participants could no longer keep pace, the last successfully performed stage was recorded. In addition, the percentile was calculated, and the target score was predicted on the basis of scores obtained from the S-test score list provided by the Ministry of Education, Culture, Sports, Science and Technology of Japan. Results and Discussion: Subjects in the >78 kg category scored significantly lower than subjects in all other groups. Similarly, subjects in the 78 kg category scored significantly lower than subjects in the 48 kg, 57 kg, and 70 kg categories. These results indicate no significant differences in subjects in the 48 kg to 70 kg categories. Conclusion: Target scores were predicted by using S-test score percentiles for female judo participants. To date however, an S-Test score list is only available for not athletes. Female judo participants can do more effective training to improve maximal oxygen uptake.